NEURAL-NETWORK MODEL OF SOFTWARE QUALITY PREDICTION BASED ON QUALITY ATTRIBUTES (Computer systems and information technologies, 2022)
The paper proposes a neural-network model of software quality prediction based on quality attributes. The proposedmodel differs from the known models, because it provides considering the importance of each quality attribute and their interactionwithin each software quality characteristic. The artificial neural network (ANN) outputs correspond to the values of software qualitycharacteristics (functional suitability, performance efficiency, usability, reliability, compatibility, security, maintainabi lity, portability).The artificial neural network (ANN) outputs make it possible assessing the total impact of quality attributes on software qualitycharacteristics
Keywords: software, software quality, software quality attributes, software quality characteristics, artificial neural network (ANN)